Co–B Nanoflakes as Multifunctional Bridges in ZnCo2O4 Micro‐/Nanospheres for Superior Lithium Storage with Boosted Kinetics and Stability. Issue 14 (21st February 2019) - Deng, Jiaojiao; Yu, Xiaoliang; Qin, Xianying; Zhou, Dong; Zhang, Lihan; Duan, Huan; Kang, Feiyu; Li, Baohua; Wang, Guoxiu
Abstract: Transition metal oxides hold great promise as high‐energy anodes in next‐generation lithium‐ion batteries. However, owing to the inherent limitations of low electronic/ionic conductivities and dramatic volume change during charge/discharge, it is still challenging to fabricate practically viable compacted and thick TMO anodes with satisfactory electrochemical performance. Herein, with mesoporous cobalt–boride nanoflakes serving as multifunctional bridges in ZnCo2 O4 micro‐/nanospheres, a compacted ZnCo2 O4 /Co–B hybrid structure is constructed. Co–B nanoflakes not only bridge ZnCo2 O4 nanoparticles and function as anchors for ZnCo2 O4 micro‐/nanospheres to suppress the severe volume fluctuation, they also work as effective electron conduction bridges to promote fast electron transportation. More importantly, they serve as Li + transfer bridges to provide significantly boosted Li + diffusivity, evidenced from both experimental kinetics analysis and density functional theory calculations. The mesopores within Co–B nanoflakes help overcome the large Li + diffusion barriers across 2D interfaces. As a result, the ZnCo2 O4 /Co–B electrode delivers high gravimetric/volumetric/areal capacities of 995 mAh g −1 /1450 mAh cm −3 /5.10 mAh cm −2, respectively, with robust rate capability and long‐term cyclability. The distinct interfacial design strategy provides a new direction for designing compacted conversion‐type anodes with superior lithium storage kinetics and stability for practical applications. Abstract : A compacted Co–B/ZnCo2 O4 hybrid structure is constructed with Co–B nanoflakes serving as multifunctional bridges in ZnCo2 O4 micro‐/nanospheres . They not only act as robust mechanical bridges to buffer the severe volume fluctuation but also work as ionic/electronic conduction bridges to accelerate the lithium storage kinetics. Compacted and thick electrodes can be fabricated with robust rate capability and long‐term cyclability.